Individual Differences in the Context of Active Learning (Teaching and Learning Inquiry, 2025)
Active learning pedagogies’ benefits for academic outcomes are well-established (Prince 2004). There is, however, evidence of individual differences in outcomes (Richardson et al. 2012). The present study considers whether gender, race, and socio-economic status (SES) relate to academic self-efficacy, perceived learning, and student engagement during the intense active learning experience of Reacting to the Past (Reacting). Students from three US universities (N = 211) completed a survey after participating in a Reacting game. The survey assessed academic self-efficacy, perceived learning, and engagement and collected student-reported demographic characteristics. Female students perceived more learning, more achievement of learning outcomes, and more enjoyment than their male peers; they also reported more engagement with the game. Students from minoritized racial groups were generally more positive about their Reacting experience than White students, especially with regard to perceived learning. Students from low socioeconomic status groups reported more engagement with the game than those from higher SES status groups.